METHODS AND MEANS OF IMPROVING THE METHODOLOGY OF TEACHING TERMINOLOGICAL LEXICON TO STUDENTS IN THE DIRECTION OF ELECTRICITY (Лучшие интеллектуальные исследования, 2025)
Annotation: This article explores various methods and tools to enhance the teaching methodology of terminological lexicon to students specializing in electricity. It emphasizes the importance of developing a clear and structured approach to teaching technical vocabulary to enhance comprehension and practical application. A combination of traditional and modern teaching tools, including technology integration, is examined to improve learning outcomes.